Graphene for Electronics - Kogan, Eugene (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Graphene is an allotrope of carbon consisting of a single layer of atoms arranged in a two-dimensional (2D) honeycomb lattice. Graphene's unique properties of thinness and conductivity have led to global research into its applications as a semiconductor. With the ability to well conduct electricity at room temperature, graphene semiconductors could easily be implemented into the existing semiconductor technologies and, in some cases, successfully compete with the traditional ones, such as silicon. This reprint presents very recent results in the physics of graphene, which can be important for applying the material in electronics.